Ammonia enhanced electrokinetics coupled with bamboo charcoal adsorption for remediation of fluorine-contaminated kaolin clay. (20th April 2016) - Zhu, Shufa; Han, Dongliang; Zhou, Ming; Liu, Yana
Abstract: The remediation of fluorine-contaminated kaolin using ammonia enhanced electrokinetics coupled with bamboo charcoal adsorption was assessed. Six electrokinetic experiments were conducted in self-made electrokinetic apparatus with deionized water as catholyte. Ammonia with concentration of 0, 0.01 and 0.1 mol/L was used as anolyte, and the voltage gradient was set at 1.0 and 1.5 V/cm. Bamboo charcoal was loaded in the central part of the electrolytic cell as adsorbent to adsorb various forms of fluorine pollutants migrating here. The effects of different ammonia concentration and voltage gradient on the removal of soil fluorine were analyzed. Ammonia enhanced electrokinetic not only increased electric current, but also changed the pH values of catholyte, anolyte and soil which made different fluorine speciation exist in soil such as anions F −, HF2 − and cations (AlF) 2+, AlF2 + . The removal of fluorine increased significantly with the concentration of the ammonia, which indicated that ammonia could facilitate soil fluorine to transform into dissolved form effectively and desorption of soil fluorine was a key limiting factor for fluorine-contaminated soil by electrokinetics. F −, HF2 −, and (AlF) 2+, AlF2 + in soil solution had opposite charges and moved in reverse direction under the function of electrokinetics, which caused fluorine pollutants to move to the central section of the electrolytic cell, where they were adsorbed exactly by the bamboo charcoal loaded there. The maximum adsorption capacity of fluorine by bamboo charcoal was 3.17 mg/g and the removal rate of soil fluorine reached 75.70%. The integration of ammonia enhanced electrokinetics with bamboo charcoal adsorption as a hybrid method was most effective for the remediation of fluorine-contaminated soil.